A new species of Werauhia (Bromeliaceae: Tillandsioideae) from the Brazilian “Hylaea” - Leme, Elton M.c.; Valsko, Jefferson J.; Krahl, Amauri H.; Grant, Jason R. (Phytotaxa, 2020)
The authors describe and illustrate Werauhia hylaeana, a new species of Tillandsioideae (Bromeliaceae) from the Amazonian “Hylaea” of Brazil. It is related to W. gladioliflora, but differs in its stature, leaf blade, and inflorescence size, in the shape of floral bracts, sepals, and petals. An identification key for the species of Werauhia reported to Brazil is presented, in addition to habitat and distribution data for the new species.